Wajib Lapor Lowongan Pekerjaan oleh Pemberi Kerja Setelah Berlakunya Peraturan Presiden Nomor 57 Tahun 2023 tentang Wajib Lapor Lowongan Pekerjaan - Ayuningtyas, Meyzia Ellena (Jurnal Ilmiah Penegakan Hukum, 2025)
This article aims to analyze the Presidential Regulation of the Republic of Indonesia Number 57 of 2023 on Mandatory Reporting of Job Vacancies. The problem is focused on the government's efforts to accomodate the available employment opportunities and rampant fraud that job seekers faced, which requires government's role in overcoming this and how mandatory reporting of job vacancies regulated after the enactment of Presidential Regulation of the Republic of Indonesia Number 57 of 2023 on Mandatory Reporting of Job Vacancies, and its comparison with Presidential Decree of the Republic of Indonesia Number 4 of 1980 on Mandatory Reporting of Job Vacancies. The data were collected through doctrinal research method and analyzed qualitatively. This study concludes that with the existence of Presidential Regulation of the Republic of Indonesia Number 57 of 2023 on Mandatory Reporting of Job Vacancies it’s hoped that job seekers can find jobs with reliable sources can match their criteria and fields they are interested in, and the government can ensure that this regulation can be implemented as regulated.